PHARMACOTHERAPY AND OUTCOMES OF ACUTE ST-ELEVATION MYOCARDIAL INFARCTION - GENDER DIFFERENCES IN REAL CLINICAL PRACTICE - P. V. Dolotovskaya; E. Y. Rudnichenko; N. V. Furman; O. V. Reshet'ko (Столичная издательская компания, 2015)
Aim. To analyze gender differences in pharmacotherapy and outcomes of ST-elevation myocardial infarction (STEMI) in patients of cardiology hospital in real clinical practice. Material and methods. A continuous pharmacoepidemiological analysis was performed on the base of 153 records of patients with STEMI (men 102, women 51), consecutively admitted to the emergency department of cardiology hospital in the period from October 2010 to April 2011.Results. Women were on average 10.6 years older than men, had significantly higher incidence of severe comorbid conditions and significantly fewer prescribed medications improving STEMI prognosis - thrombolytics (21% vs 50%; p<0.05), statins (20% vs 53%; p<0.05), beta-blockers (84% vs 91%; p<0.05) and dual antiplatelet therapy (21% vs 59%; p<0.05). Hospital mortality was significantly higher in women than this in men, at that mortality differences persisted for 12 months after discharge.Conclusion. Older age, higher comorbidity rate, and lower treatment compliance with the current clinical recommendations in female STEMI patients in comparison with these in male STEMI patients contribute to higher hospital mortality and 12-month mortality after discharge in women with STEMI.